Analisis Kerentanan Sosial Gempabumi Di Kecamatan Gantiwarno Kabupaten Klaten - HASTUTI, DWI PUJI, Dr. Kuswaji Dwi Priyono M.Si (2017)
Society is one of the important elements in measuring the risk of a disaster event. There are four types of vulnerabilities: physical, social, economic, and environmental vulnerability. The social vulnerability of the people should be given important attention in efforts to reduce the risk of earthquakes.Earthquake until now is a natural disaster that can not be predicted when the occurrence accurately, so that there is an effort to minimize the vulnerability of the community. These efforts are one of them by minimizing the level of social vulnerability.Social vulnerability is often overlooked in the earthquake disaster management process, some of which are focused more often on knowledge of building structures and physical problems (Flanagan et al., 2011).Analysis of social vulnerability is the state of an area affected by physical, social, cultural, environmental to prevent, dampen in response to disaster. Determination of social vulnerability indicators using three variables, namely the poverty of the population, the elderly and under-five population, female supporters.The result of the research shows the level of social class of moderate, low, high earthquake vulnerability and the correlation of social vulnerability with earthquake vulnerability in Gntiwarno Sub-district of KlatenRegency.Test results on three variables are known that, Firstly, based on tabular data processing results using ArcGIS software, the highest social vulnerability is found in six villages namely Baturan village with population density 1464 Soul / Km2, Ngandong 1420 Soul / Km2, Kragilan 1158 Soul / Km2 , Karangturi 1563 Soul / Km2, Ceporan 1550 Soul / Km2, Mutihan 1509 Soul / Km2, Muruh 1747 Soul / Km2.While for Low vulnerability exist in five villages such as Gentan village with population density 829 Soul / Km2, Sawit 1080 Soul / Km2, Jogoprayan 1076 Soul / Km2, Kerten 1088 Soul / Km2, Jabung 1093 Soul / Km2.Secondly, based on the elderly and under five population, it is known that the highest vulnerability area is Mutihan village with the number of elderly and toddlers is 748 people (8.72%); While the area with the lowest level of social vulnerability among the elderly and under-five population is Gentan Village with an elderly and under-five population of 298 people (3.47%).Third, the level of social vulnerability to earthquake disasters in KecamatanMewwarno based on female population is known that Kragilan village is an area with social vulnerability to earthquake disaster based on the lowest population of women, it is known that the number of female population in the village of Kragilan fewer If compared to the male population is 885 people, while for the area with the highest level of social vulnerability with the greater number of women than men is Kerten Village, this is because the ratio of the number of women to men is 90.21%.With relatively difficult terrain, in the event of a disaster the female population is usually relatively more vulnerable than the male population.